Revamping occupational safety and health training: Integrating andragogical principles for the adult learner (Construction Economics and Building, 2013)
Despite attempts to improve safety performance, the construction industry continues to account for a disproportionate rate of injuries. A large proportion of these injuries occur because workers are unable to recognize and respond to hazards in dynamic and unpredictable environments. Unrecognized hazards expose workers to unanticipated risks and can lead to catastrophic accidents. In order to enhance hazard recognition skills, employers often put new and experienced workers through formal hazard recognition training programs. Unfortunately, current training programs primarily rely on instructor-centric pedagogical approaches, which are insensitive to the adult learning process. In order to ensure effective adult learning, training programs must integrate learner-centric andragogical principles to improve engagement and retention in adult trainees. This paper aims to discuss training program elements that can potentially accelerate the adult learning process while improving safety knowledge retention. To this end, the researchers reviewed relevant literature on the cognitive processes of adult learning, essential components of effectual training programs and developed a reliable framework for the training and transfer of safety knowledge. A case example of successfully using the framework is also presented. The results of the study will provide safety trainers and construction professionals with valuable information on developing effective hazard recognition and receptor training programs, with the goal of improving construction safety performance.